That feeling I get: Examination of the exercise intensity-affect-enjoyment relationship. (March 2018) - Greene, Daniel R.; Greenlee, Tina A.; Petruzzello, Steven J.
Abstract: While affective responses to aerobic exercise are fairly well documented, only recently have affective responses to high-intensity interval exercise (HIIE) been examined. Objective: Evaluate affective responses before, during, and following, as well as enjoyment following, moderate intensity continuous exercise (MICE) and body weight interval exercise (BWIE), along with an inactive control. Methods: Participants ( N  = 366; 215 females; 20.6 ± 2.3 yrs) were relatively active (76.8% reported exercising vigorously on a regular basis), and completed randomly ordered 15-min conditions: Walking (MICE), Quiet Reading (READ), BWIE (2 min activity, 1 min recovery). Affective state (Energy, Tiredness, Tension, Calmness) was assessed before (Pre), immediately after (Post-0), and 20 min after (Post-20) each condition; Enjoyment was assessed post condition only. Valenced affect (Feeling Scale; FS) was assessed Pre, during, Post-0, and Post-20. Results: Affect changed from Pre to Post-0 with Condition x Time interactions (all p s  < 0.001, Cohen's d s  = 0.17 to 1.9) for all measures, reflecting improved affective state following BWIE and MICE relative to READ. FS progressively decreased during BWIE, but was significantly greater Post-20 relative to Pre. During MICE, FS increased and remained elevated at Post-20. Post exercise enjoyment was not different between BWIE and MICE, but both resulted in greater enjoyment relative to READ. Further, after accounting for age, sex, and baseline FS, in-task FS predicted significant unique variance in enjoyment for each condition ( p s  < 0.001). Conclusion: These findings suggest BWIE, a variant of HIIE, is well-tolerated and results in similar enjoyment as moderate intensity continuous exercise. Additionally, while in-task affect declined during BWIE, affective valence was still positive throughout and was improved in both BWIE and MICE Post-20. BWIE may be an enjoyable alternative to more traditional steady state aerobic exercise, producing similar enjoyment and psychological benefits. Highlights: Compared body weight interval exercise (BWIE), moderate-intensity continuous exercise (MICE), and control (READ) on affect. Evaluated enjoyment following BWIE, MICE, and READ conditions. For enjoyment, BWIE was not different from MICE, but both resulted in significantly greater enjoyment relative to READ. Affective valence decreased during BWIE and READ, but increased during MICE. Valence increased during recovery from BWIE and MICE. In-task affective valence predicted enjoyment, explaining ~20% unique variance. BWIE may be enjoyable alternative to moderate intensity exercise, producing similar enjoyment and psychological benefits.